A RETROSPECTIVE COHORT STUDY OF 200 PATIENTS: CLINICAL MANIFESTATIONS AND AETIOLOGY OF RECURRENT CORNEAL EROSION SYNDROME. - Singh, Niharika; Singh, Arjun Kumar (Student’s Journal of Health Research Africa, 2024)
Objective To investigate the clinical characteristics and causes of recurrent corneal erosion syndrome (RCES). Methods A study was conducted on 200 patients (185 eyes) diagnosed with Recurrent Corneal Erosion Syndrome (RCES) at the institution, Netaji Subhas Medical College and Hospital, Bihta, Patna. The analyzed data encompassed information on demographics, causes, position on the cornea, and the relationship with meibomian gland dysfunction (MGD). Findings The average age of participants was 44.5 years, with a range of 14-80 years. The identified causes of Recurrent Corneal Erosion Syndrome (RCES) were as follows: prior minor trauma (73 eyes, 39.45%), photorefractive keratectomy (31 eyes, 16.75%), epithelial basement membrane corneal dystrophy (EBMD) (31 eyes, 16.75%), laser-assisted in situ keratomileusis (14 eyes, 7.56%), and unknown origin (36 eyes, 18.91%). The inferior paracentral cornea was the most common area for recurrent corneal erosions (RCES), accounting for 68.4% of cases. The upper cornea and other locations were less frequently affected, with each accounting for 21.3% of cases. MGD was present in 59% of patients. Summary Recurrent corneal erosion syndrome (RCES) can be caused by many factors, which account for the diverse range of symptoms observed in individuals with the condition. Notably, a considerable proportion of patients with Recurrent Corneal Erosion disease (RCES) start experiencing the disease after undergoing keratorefractive surgery, a significant proportion of individuals also exhibit Meibomian Gland Dysfunction (MGD). Recommendations The study suggests treating MGD, which is often connected to RCES. It also suggests treating RCES with PRK and LASIK and preventing it in patients. Study MGD’s role in RCES and treatment options including phototherapeutic keratectomy (PTK), which has shown promise in managing reoccurring cases.